INDONESIA DALAM MENGHADAPI PERBATASAN LAUT (PERSPEKTIF ILMU SOSIAL) - Alwi Usra Usman; Andi Agustang; Idham Irwansyah Idrus (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2023)
Indonesian is located in the equatorial region,between the continents of Asia and Australia which exclusively connects the economies of developed countries. In addition, Indonesia is also located between 2 oceans, namely the Pacific and the Indian Ocean, which makes a connecting area between countries in East Asia and Southeast Asia and South Asia. The purpose of this study is to find out: (1) problems and problems solving regarding the emergence of maritime terrorism issues from a social science perspective. (2) problems and solutions to Indonesia’s problems in realizing the vision of the world’s maritime axis from a social science perspective.This study uses defense theory from Brigadier General (Purn) Makmur Supriyanto in his book “About Defense Science” and sea power theory from Alfred Thayer Mahan using secondary data, data collection techniques through library research and qualitative data analysis to reach conclusions. Based on the result of the research, it shows that since the collapse of the WTC building in September 2011 and the Bali bombing, Indonesia has provided information on terrorism and activelty participated in the war on terror policy proclaimed by the United States. From a social science perspective, Indonesia can minimize the emergence of maritime terrorism issues using defense theory. The main idea of the vision of the world maritime axis is to develop maritime characteristics and emphasize the “archipelagic book” namely the insight that Indonesian waters are an economic potential and national strength. From a social science perspective, Indonesia can realize the vision of the world’s maritime axis by using the sea power theory. From the two problems described above, we can solve both using the concept of maritime security.